The Accentuation of Three-Word ‘ כִּי Clauses’ Ending with Silluq and Atnaḥ - Hitin-Mashiah, Rachel (Vetus Testamentum, 2015)
In several verses in the Hebrew Bible the Atnaḥ is preceded by two conjunctives. In these cases both words preceding the Atnaḥ are accented by Munaḥ. This uncommon pattern Munaḥ–Munaḥ–Atnaḥ almost always begins with the word כִּי, as can be seen in the clause כִּ֣י ט֣וֹב פָּתָ֑ר (Gen 40:16). In this paper I examine and clarify some prosodic rules concerning the uncommon as well as the common accentuation of three-word ‘כִּי clauses’ ending with Atnaḥ and Silluq.